Itinerario de una lista. De la Hispania visigoda a Italia beneventana, del Liber Iudiciorum al Pseudo-Isidoro - William Trouvé (Medievalista)
This article deals with a copy of a visigothic regnal list, which is found in two manuscripts of Pseudo-Isidore: Montecassino, ms. 1 and Paris, BnF, lat. 1557. The visigothic regnal list/canon law association is surprising because the list was created with the Liber Iudiciorum, a visigothic legal code, published in 654. Moreover, the list from both these codices has modifications: the names of Gregory the Great, the emperor Maurice and the bishop Isidore of Seville were added. We propose to identify the manuscript difusion of the list, in relation to the Liber Iudiciorum and the Pseudo-Isidore, as well as to interpret these deliberate modifications.